Low-carbon agriculture in South America to mitigate global climate change and advance food security - Moraes Sa, Joao Carlos de; Lal, Rattan; Cerri, Carlos Clemente [UNESP]; Lorenz, Klaus; Hungria, Mariangela; Faccio Carvalho, Paulo Cesar de (Elsevier B.V., 2017)
The worldwide historical carbon (C) losses due to Land Use and Land-Use Change between 1870 and 2014 are estimated at 148 Pg C (1 Pg = 1 billion ton). South America is chosen for this study because its soils contain 10.3% (160 Pg C to 1-mdepth) of the soil organic carbon stock of the world soils, it is home to 5.7% (0.419 billion people) of the world population, and accounts for 8.6% of the world food (491 million tons) and 21.0% of meat production (355 million tons of cattle and buffalo). The annual C emissions from fossil fuel combustion and cement production in South America represent only 2.5% (0.25 Pg C) of the total global emissions (9.8 Pg C). However, South America contributes 31.3% (0.34 Pg C) of global annual greenhouse gas emissions (1.1 Pg C) through Land Use and Land Use Change. The potential of South America as a terrestrial C sink for mitigating climate change with adoption of Low-Carbon Agriculture (LCA) strategies based on scenario analysis method is 8.24 Pg C between 2016 and 2050. The annual C offset for 2016 to 2020, 2021 to 2035, and 2036 to 2050 is estimated at 0.08, 0.25, and 0.28 Pg C, respectively, equivalent to offsetting 7.5, 22.2 and 25.2% of the global annual greenhouse gas emissions by Land Use and Land Use Change for each period. Emission offset for LCA activities is estimated at 31.0% by restoration of degraded pasturelands, 25.6% by integrated crop-livestock-forestry-systems, 24.3% by no-till cropping systems, 12.8% by planted commercial forest and forestation, 4.2% by biological N fixation and 2.0% by recycling the industrial organic wastes. The ecosystem carbon payback time for historical C losses from South America through LCA strategies may be 56 to 188 years, and the adoption of LCA can also increase food andmeat production by 615 Mton or 17.6 Mton year(-1) and 56 Mton or 1.6 Mton year(-1), respectively, between 2016 and 2050. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Greenhouse gas; Best agricultural management practices; C-offset; Land use and land use change